2021
DOI: 10.1016/j.trd.2021.102950
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing heterogeneity in passenger satisfaction, loyalty, and complaints with air-rail integrated services

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…It means passenger satisfaction affects passenger loyalty. According to Yuan et al (2021), passenger satisfaction and impact on loyalty and user complaints indicate that several groups of passengers share common interests in ticketing services, reliability, accessibility, and convenience. While some striking differences in perceptions are identified in personalized services, information services, and connectivity.…”
Section: Passenger Satisfaction Affects Passenger Loyaltymentioning
confidence: 99%
“…It means passenger satisfaction affects passenger loyalty. According to Yuan et al (2021), passenger satisfaction and impact on loyalty and user complaints indicate that several groups of passengers share common interests in ticketing services, reliability, accessibility, and convenience. While some striking differences in perceptions are identified in personalized services, information services, and connectivity.…”
Section: Passenger Satisfaction Affects Passenger Loyaltymentioning
confidence: 99%
“…In particular, Choi et al (2021) found that commute satisfaction is heterogeneous among people with different attitudes toward commuting. Yuan et al (2021) found that reliability, ticket service, operation schedule, and connectivity of integrated air-rail services affect satisfaction of all intermodal passengers, while the key correlates of satisfaction varies among different passenger groups. Finally, different from most studies that are primarily based on survey data, Koller (2021) relied on a driving simulator to study the affective judgment of drivers in different route scenarios using an experimental design.…”
Section: • New Methods In Travel Satisfaction Researchmentioning
confidence: 99%
“…In this research, we would like to make evaluations of passengers' satisfaction with existing IABS. Therefore, the use of the realexperience-based RP data is considered a more accurate source for satisfaction analysis (Gao et al, 2021;Yuan et al, 2021aYuan et al, , 2021b.…”
Section: Data Collecting Methods For Passenger Satisfactionmentioning
confidence: 99%
“…• Integration. Inspired by IARS, integrations of (a) ticketing (Efthymiou and Antoniou, 2017;Guan et al, 2020), (b) information (Li et al, 2018;Merkert and Beck, 2020), (c) schedule (Lu et al, 2016;Wu et al, 2015;Xia and Zhang, 2017), (d) transfer efficiency (Jiang et al, 2021;Li and Sheng, 2016;Socorro and Viecens, 2013), and other services such as check-in and luggage handling (Yang et al, 2022;Yuan et al, 2021aYuan et al, , 2021b should be key indicators for satisfaction under the air-bus context.…”
Section: Passenger Satisfaction With Iabsmentioning
confidence: 99%
See 1 more Smart Citation